Peran Corporate Governance Dan Audit Terhadap Integritas Laporan Keuangan Perusahaan Transportasi Yang Terdaftar Di BEI Tahun 2020–2023 - Putri Surya Fatiha; Muhammad Ridha Habibi Z; Taufik Hidayat; Esa Setiana (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to analyze the effect of corporate governance structure, proxied by the Audit Committee, Independent Commissioners, Audit Tenure, Size of Public Accounting Firms, and Auditor Turnover, on the Integrity of Financial Statements in transportation companies listed on the Indonesia Stock Exchange for the period 2020–2023. This study uses a quantitative approach with secondary data in the form of company annual reports. The sample was determined using purposive sampling and analyzed using multiple linear regression. The results show that the Audit Committee, Independent Commissioners, Audit Tenure, and Public Accounting Firm Size have a significant effect on Financial Statement Integrity, while Auditor Turnover does not have a significant effect. Simultaneously, all independent variables affect financial statement integrity. These findings reinforce agency theory, which states that internal and external oversight mechanisms play a role in minimizing conflicts of interest and improving the credibility of financial reporting.